The Principles and Practice of Modal Counterpoint. - Green, Douglass (Taylor & Francis, 2010)
Covering modal music from Gregorian chant through the seventeenth century, The Principles and Practice of Modal Counterpoint is a comprehensive textbook combining stylistic composition, theory and analysis, music history, and performance. By supplementing a modified species approach with a wealth of complete musical examples and historical information, this textbook thoroughly joins principle with practice, providing a truly immersive experience in the study of modal counterpoint and familiarizing students with modal repertoire.